Diagnostic criteria to differentiate pathological procrastinators from common delayers: a re-analysis - Rist, Fred; Engberding, Margarita; Hoecker, Anna; Wolf-Lettmann, Johanne; Fischbach, Eva-Maria (Frontiers in Psychology, 2023)
Detection and treatment of clinically relevant forms of procrastination would be greatly facilitated by diagnostic criteria as formulated for psychological disorders in the Diagnostic and Statistical Manual (DSM-5). In the present article, the steps for deriving and validating diagnostic criteria for pathological procrastination are described. In an online survey of a random sample of N = 10,000 German university students, 990 answered 13 items derived from the attempts in the literature to define procrastination, the Aitken Procrastination Inventory (API) and the Patient Health Questionnaire (PHQ-9). A subset of six items related to the first factor onset delay of the API was selected by Best Subset Multiple Regression (BSMR). A latent class analysis (LCA) of these six items sorted the students into six clusters. A cluster of pathological procrastinators (10%) was separated from the clusters of less impaired habitual, average, and occasional delayers. In addition, a cluster of unconcerned delayers (10%), with strong procrastination tendencies but little personal disadvantages, and a small cluster of fast performers (2%) emerged. The pathological procrastinators differed from all other clusters significantly on nine of the 13 items. They were older, had studied longer but had fulfilled less of their study obligations and were more depressed. The answer options of the six questions were collapsed into two categories (procrastination feature present for at least half a year or absent). These criteria were used for the clinical diagnosis of pathological procrastination. For a diagnosis, two fixed criteria (delaying important tasks needlessly and strong interference with personal goals) plus at least two of four additional criteria (time spent procrastinating, time pressure, physical and psychological complaints, below performance potential) must be met. This diagnostic rule captured 92% from the cluster of pathological procrastinators and 10% of the habitual delayers, but no one from the remaining clusters. Using these diagnostic criteria for clinical diagnosis and intervention decisions will facilitate the comparison and integration of the results from future studies of procrastination.